A Pragmatic Analysis of Politeness Strategies in WhatsApp Groups - Tobias Gunas; Hieronimus Canggung Darong; Thi Loan Lam (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This study aimed to analyze the politeness strategies used in WhatsApp Group communication among university students. The research employed a qualitative descriptive design with a pragmatic approach based on Brown and Levinson’s politeness theory. The participants of the study consisted of 25 students who actively interacted in an academic WhatsApp Group. The data were collected through documentation of naturally occurring conversations in the WhatsApp Group, including requests, reminders, greetings, apologies, suggestions, and discussions. The researcher functioned as the primary research instrument, while supporting instruments included observation notes, documentation sheets, and coding categories. The data were analyzed qualitatively through data reduction, classification, interpretation, and conclusion drawing based on the four categories of politeness strategies proposed by Brown and Levinson: bald-on-record, positive politeness, negative politeness, and off-record strategies. The findings revealed that all four types of politeness strategies were employed by the participants in WhatsApp Group communication. Positive politeness strategy was the most dominant strategy, accounting for 40% of the data, followed by the negative politeness strategy (27%), bald-on-record strategy (20%), and off-record strategy (13%). The findings indicate that participants tended to emphasize solidarity, cooperation, friendliness, and harmonious interaction in digital communication. In addition, the study found that contextual factors and digital communication features such as emojis and informal expressions contributed to the realization of politeness strategies. Overall, this study confirms that politeness remains an important aspect of interpersonal communication in technologically mediated interaction and demonstrates the relevance of pragmatic analysis in understanding digital communication practices